Pendekatan Maqāṣid al-Qur’an dan Maqāṣid Shariah dalam Pembelajaran al-Qur’an Hadis di Madrasah Aliyah - Tiara Wardatutsaniyah; Hanun Asrohah; Husniyatus Salamah Zainiyati (Bustanul Ulum Journal of Islamic Education, 2026)
Contemporary Islamic education faces the challenge of moving beyond literalist and rigid approaches toward contextual learning. This study addresses this issue by formulating a synergistic framework that integrates maqāṣid Al-Qur’an (textual divine objectives) and maqāṣid al-sharī‘ah (five essential preserves of human interest) into Qur'an-Hadith learning. Employing a qualitative research design with a conceptual analysis approach, data were gathered through document analysis of classical-contemporary hermeneutical literature and the standard Madrasah Aliyah Qur'an-Hadith curriculum. The study reveals that synthesizing both maqāṣid dimensions creates a holistic pedagogical framework. While maqāṣid Al-Qur’an unlocks the intrinsic wisdom of textual verses and prophetic traditions, maqāṣid al-sharī‘ah categorizes these messages into structured societal preservation goals (faith, life, intellect, lineage, and wealth). Consequently, learning methods shift from passive memorization to inquiry-based, problem-solving, and reflective models. The impact of this synergy is the cultivation of a maqāṣidi pedagogical disposition, enabling students to bridge sacred texts with modern realities. However, as a conceptual inquiry, this study is limited by the absence of empirical classroom implementation. In conclusion, integrating maqāṣid Al-Qur’an and maqāṣid al-sharī‘ah transforms Qur'an-Hadith instruction into a dynamic, relevant, and value-oriented educational paradigm